Evaluating Growth Performance and Feed Cost Economics of Japanese Quails Fed with Varying Levels of Guar Meal - Guntaka; Kumar Chitithoti, Anil; Kishore Konka, Raja; Thullimalli, Susmita; Suratani, Sreedhar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A study was conducted to evaluate the inclusion of guar meal (GM) as a partial replacement for soybean meal (SBM) in Japanese quail diets. 150-day-old chicks were randomly assigned to five dietary treatments: T1 (0% GM), T2 (2% GM), T3 (4% GM), T4 (6% GM) and T5 (8% GM), with three replicates per treatment (10 birds each). Feed intake, body weight gain (BWG), and feed conversion ratio (FCR) were recorded weekly, and cost-effectiveness was assessed based on current local market prices. Results revealed that BWG significantly improved (p<0.01) with GM inclusion, peaking at 6% (T4) before declining at 8% (T5). Feed intake increased linearly with GM levels but showed no significant differences between treatments (p>0.05). FCR was significantly better (p<0.01) in quails fed 6% GM (T4) compared to the control (T1), although efficiency declined at 8% GM (T5). The performance index (PI) and Protein efficiency ratio (PER) followed a similar trend, with T4 exhibiting the highest PI, PER values. Economic analysis indicated that diets containing up to 6% GM were cost-effective compared to the control, without compromising growth performance. In conclusion, guar meal can be incorporated into quail diets at levels up to 6% as a cost-effective alternative to soybean meal, enhancing growth performance and feed efficiency. Higher inclusion levels (≥8%) are not recommended due to adverse effects on performance metrics.